Characterizing Oral Synthetic Nicotine Pouch Use in Post-Secondary Students. - Turner, William G.; Natarajan, Bhagya; Bignell, Elizabeth M.; Lewis, Nicole; Adeseiye, Stephanie; Sladen-Dew, Claerwen; James, Matthew D.; Hopman, Wilma M.; Neder, J. Alberto; Rodriguez-Llamazares, Sebastian; Domnik, Nicolle J. (Journal of Community Health, 2025)
Synthetic oral nicotine pouches (ONP) are an increasingly popular route for non-tobacco nicotine consumption. While there is a growing understanding of ONP use internationally, especially in countries where these products have been available longer, few studies address ONP use in Canada. This cross-sectional study sought to quantify and characterize current ONP use in Canadian post-secondary students. A Qualtrics-based web survey of Canadian post-secondary (university or college) students was conducted in September/October 2024. This collected demographics, participant ONP history, recent use, and other nicotine/non-nicotine substance use. The Penn State Nicotine Pouch Dependence Index (PSNPDI) was embedded within the broader survey to assess nicotine dependence. Descriptive analysis was performed for ever- and recent-ONP use prevalence, poly-use of ONP with other products/substances, and ONP use with key demographic or contextualizing factors. Of 452 post-secondary student respondents (22% male, 78% female; age: 20.2 ± 2.6y), 27% reported ever-use of ONPs, with a mean ± SD age at first use of 19.2 ± 3.0y and 12% of all respondents reporting ONP use in the last 30 days. 77% and 89% of ONP users reported ever-use of tobacco and e-cigarettes, respectively, versus 24% and 44% of non-ONP users (p < 0.001). Among ONP ever-users, 62.3% reported no (PSNPDI score 0–3), 29.5% reported low (PSNPDI score 4–8), and 8.2% reported medium (PSNPDI score 9–12) dependence. These data provide a first glimpse into ONP use in Canadian post-secondary students, against which to assess future use patterns.